Developing Instagram-Based E-Poster for Learning the Concept of Alkaline Group of Periodic Table - Muhammad Nazar; Ratu Fazlia Inda Rahmayani; Diwana Aida; Kana Puspita (Postgraduate, University of Mataram, 2021)
This research aimed at developing e-poster as learning media, analyzing how students respond to the e-posters uploaded to Instagram. This R&D research utilized an ADDIE model of development consisting of five stages: analysis, design, development, implementation, and evaluation. The research took place during even semester at the Department of Chemical Education, Faculty of Education and Teacher Training, Universitas Syiah Kuala. A total of twenty-four students (4 male and 20 female) who enrolled in the course of